Perbandingan skor Middle Ear Risk Index (MERI) pada pasien Otitis Media Supuratif Kronis (OMSK) dengan komplikasi intrakranial dan ekstrakranial di RSUD dr. Saiful Anwar, Malang, Indonesia - Ahmad Dian Wahyudiono; David Santoso (Intisari Sains Medis, 2022)
Background: Chronic Suppurative Otitis Media (CSOM) is a chronic infection in the middle ear mucosa with tympanic membrane perforation and causes complications in the form of intracranial and extracranial. In previous studies, CSOM mortality rates were different between intracranial and extracranial complications. That prompted the researchers to determine the middle ear postoperative prognosis in CSOM with intracranial complications compared to the extracranial. Postoperative prognosis is measured by Middle Ear Risk Index (MERI). This study aims to evaluate the comparison of MERI scores in CSOM patients with intracranial and extracranial complications. Methods: The research was conducted with an observational analytic design involving 40 research subjects from medical records of CSOM patients at RSUD dr. Saiful Anwar Malang in January 2017 – July 2021. The samples were divided into CSOM with intracranial and extracranial complications, including 12 and 28 subjects, respectively. Those samples are taken using consecutive sampling techniques and tested using an Independent T-test. Data were analyzed using SPSS version 25 for Windows.Results: The mean of MERI scores in CSOM patients with intracranial complications was 9.170±2.517, and that in extracranial complications was 7.570±1.854. The p-value of 0.031 (P<0.05) was obtained using an Independent T-test, indicating a significant difference of MERI scores mean between CSOM patients with intracranial and extracranial. Conclusion: There is a significant difference in MERI scores between CSOM with intracranial and extracranial complications. Latar Belakang: Otitis Media Supuratif Kronis (OMSK) adalah infeksi kronis yang terjadi pada mukosa telinga tengah yang ditandai dengan perforasi membran timpani dan dapat menyebabkan komplikasi intrakranial maupun ekstrakranial. Penatalaksanaan OMSK dengan komplikasi bertujuan untuk menyelesaikan komplikasi, infeksi di telinga tengah dan perbaikan fungsi. Perbaikan fungsi pendengaran bukan tujuan utama tapi tetap menjadi harapan dari pasien. Prognosis fungsi pendengaran pada operasi mastoid dapat dinilai dengan memperhatikan Middle Ear Risk Index (MERI). Penelitian ini bertujuan untuk mengevaluasi perbandingan skor MERI pada pasien OMSK dengan komplikasi intrakranial dan ekstrakranial.Metode: Penelitian dilakukan dengan desain penelitian observasional analitik yang melibatkan 40 subjek penelitian berupa rekam medis pasien OMSK di RSUD dr. Saiful Anwar Malang bulan Januari 2017 – Juli 2021. Sampel terbagi menjadi dua kategori yaitu OMSK dengan komplikasi intrakranial dan ekstrakranial dengan jumlah secara berurutan yaitu 12 dan 28 sampel. Sampel diambil menggunakan teknik konsekutif dan diuji menggunakan Independent T-Test. Data dianalisis dengan SPSS versi 25 untuk Windows.Hasil: Didapatkan rerata pasien OMSK dengan komplikasi intrakranial sebesar 9,170±2,517 dan ekstrakranial sebesar 7,570±1,854. Pada uji Independent T-Test didapatkan nilai p sebesar 0,031 (p<0,05) yang menunjukkan terdapat perbedaan rerata MERI pada pasien OMSK dengan komplikasi intrakranial dan ekstrakranial secara bermakna.Kesimpulan: Terdapat perbedaan skor MERI yang bermakna antara OMSK dengan komplikasi intrakranial dan ekstrakranial.